2020
DOI: 10.2147/cmar.s227415
|View full text |Cite
|
Sign up to set email alerts
|

<p>Allylated Curcumin Analog CA6 Inhibits TrxR1 and Leads to ROS-Dependent Apoptotic Cell Death in Gastric Cancer Through Akt-FoxO3a</p>

Abstract: Background: Gastric cancer is one of the leading causes of cancer-related deaths. Allylated monocarbonyl analogs of curcumin (MACs) have been reported to selectively inhibit a broad range of human cancers including gastric cancer. However, the precise molecular mechanisms underlying the inhibitory activities of MACs are not fully known. Methods: In this study, we examined the anti-tumor activities of an allylated MAC, CA6, on gastric cancer cells and gastric cancer xenograft mouse model. The potential molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“… 2014 ; Rajamanickam et al. 2020 ). Moreover, TNF-α can induce the immune response to generate cytotoxic metabolites, suppress gastric microcirculation and delay the recovery (Verma and Kumar 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“… 2014 ; Rajamanickam et al. 2020 ). Moreover, TNF-α can induce the immune response to generate cytotoxic metabolites, suppress gastric microcirculation and delay the recovery (Verma and Kumar 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies also demonstrated that allylated MAC (curcumin analogue) and CA6, blocked the development of gastric cancer cells. Specifically, CA6 binds directly to TrxR1 and inhibits its activity, resulting in ROS aggregation in gastric cancer cells (Rajamanickam et al, 2020)…”
Section: Curcumin Inhibitory Action In Different Types Of Cancermentioning
confidence: 99%
“…Various anticancer agents have been shown to promote ROS generation in cancer cells. 32,33 Study by Rajamanickam et al 20 indicates that allylated curcumin analog CA6 directly binds to and inhibiting the activity of TrxR1 resulting in the increase of ROS. Others suggest that Chinese chemical like ginsenoside Rh4, Luteolin may disturb the mitochondria function to promote the production of ROS.…”
Section: Dovepressmentioning
confidence: 99%
“…13 Studies had demonstrated that targeting the oxidative stress-mediated ER stress is one of the effective strategies for tumor therapy. [18][19][20] Yang et al 18 found that ω-Hydroxyundec-9-enoic acid induced apoptosis through ROS-mediated endoplasmic reticulum stress in non-small cell lung cancer cells. Wu et al 19 indicated that bicyclol exerted an anti-tumor effect via ROS-mediated ER stress in human renal cell carcinoma cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation